Comparative analysis of reparative dentinogenesis in an experimentally formed model of deep caries treatment - V. A. Ivashchenko; A. A. Adamchik (LLC "Endo Press", 2020)
Aim. The study of the state of the mineral component, the microhardness of the dentin, the structure of the dentin and the pulp of the lower incisors during the filling of the experimentally formed deep cavities of the CH and TheraCal LC have been carried out. This article is devoted to the morphological changes in the application of calcium hydroxide (CH) in comparison with the modern material "TheraCal LC" (Bisco) on the experimentally formed model of deep caries in rams. Material and mothods. The duration of the observation from the beginning of the experiment has been taken as 15, 30 and 90 days.Results. It was to have indicated that the basis of pathogenetic therapy should not only be necroectomy of the dentine tissue and impact on the pathogenic microflora, but also stimulation of dentinogenesis as a factor required for the formation of a highly mineralized barrier between the filling and a functioning pulp of the tooth.